Aggregation‐induced emission luminogens for organic light‐emitting diodes with a single‐component emitting layer. Issue 1 (23rd April 2022) - Hwang, Jinhyo; Nagaraju, Peethani; Cho, Min Ju; Choi, Dong Hoon
Abstract: Organic light‐emitting diodes (OLEDs) have garnered increasing attention as a promising candidate for application in next‐generation displays and solid‐state lighting devices. The doping technique commonly used to fabricate light‐emitting layers (EMLs) of OLEDs disperses the emitting material in a host matrix to mitigate aggregation‐induced quenching (ACQ). Alternatively, owing to their high efficiency and ease of manufacture, nondoped OLEDs have been developed as a substitute for doped OLEDs. When fabricating nondoped OLEDs, it is essential to suppress the ACQ effect in the EML and efficiently utilize the generated excitons for radiative decay. Since the discovery of aggregation‐induced emission (AIE) by Tang et al., significant work has been done to improve the stability and efficiency of nondoped OLEDs based on fluorescent AIE luminogens (AIEgens). Fluorescent AIEgens, synthesized using various molecular frameworks, such as silole, tetra/triphenylethylene, tetraphenylpyrazine, and tetraphenylbenzene, exhibit high photoluminescence quantum yields in the solid state. Therefore, many studies have reported that fluorescent AIEgen‐based OLEDs have excellent external quantum efficiency and exhibit emission at various wavelengths, including deep‐blue/blue/green emission. With the development of fluorescent AIEgens, delayed fluorescent AIEgens with efficient triplet utilization through reverse intersystem crossing and AIE properties have been adopted as ideal emitters and used in nondoped OLEDs. This review systematically discusses and summarizes recent reports on the development of AIEgens for nondoped OLEDs by grouping them into fluorescent and delayed fluorescent AIEgens. The purpose of this review is to provide deep insights into the design of novel AIEgens for high‐performance nondoped OLEDs. Abstract : A comprehensive overview of the development of AIE luminogens for nondoped OLEDs is presented. This article provides the molecular design strategies as well as photophysical and electroluminescent properties of AIEgens used in nondoped OLEDs. The results of studies on nondoped OLEDs based on fluorescent and delayed fluorescent AIEgens are summarized. The correlation between molecular structures, optical, and device properties in AIE‐based fluorescent and TADF emitters are analyzed.